2016
DOI: 10.1088/1674-1056/25/8/088901
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bus stop with left-turn lines between two adjacent signalized intersections

Abstract: Based on the symmetric two-lane Nagel-Schreckenberg (STNS) model, a three-lane cellular automaton model between two intersections containing a bus stop with left-turning buses is established in which model the occurrences of vehicle accidents are taken into account. The characteristics of traffic flows with different ratios of left-turn lines are discussed via the simulation experiments. The results indicate that the left-turn lines have more negative effects on capacity, accident rate as well as delay if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Overtaking speed was calculated with the following equation with probability P ov V f thickmathspace= thickmathspacemin )(G 1 + 1 + G 2 , thickmathspaceV fmaxwhere G 2 is the space available before slow vehicles and G 1 is distance between fast and slow vehicle[43, 44]1opendriver behaviour of vehicles approaching traffic light were modelled[39]2openCA model to study straight‐through movements of heterogeneous bicycle traffic at signalised intersection. Model was validated with field data[45]1opendriver behaviour affected by pedestrian violations were studiedlane change and direction[14]3openvehicles and pedestrians were modelled at intersectiononly direction changeinvestigated the effects of turning vehicles (both left and right) on the performance of intersection[18]2opena three lane signalised intersection based on NS CA model including left turning buses and occurrences of accidents, field validation wa...…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overtaking speed was calculated with the following equation with probability P ov V f thickmathspace= thickmathspacemin )(G 1 + 1 + G 2 , thickmathspaceV fmaxwhere G 2 is the space available before slow vehicles and G 1 is distance between fast and slow vehicle[43, 44]1opendriver behaviour of vehicles approaching traffic light were modelled[39]2openCA model to study straight‐through movements of heterogeneous bicycle traffic at signalised intersection. Model was validated with field data[45]1opendriver behaviour affected by pedestrian violations were studiedlane change and direction[14]3openvehicles and pedestrians were modelled at intersectiononly direction changeinvestigated the effects of turning vehicles (both left and right) on the performance of intersection[18]2opena three lane signalised intersection based on NS CA model including left turning buses and occurrences of accidents, field validation wa...…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
“…Further, various vehicle types can generate different emissions which is another reason to study heterogeneity. A few authors have included two or more modes in their study [14, 17, 18, 64].…”
Section: Literature Review Of the Ca Model At The Intersectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ming-bao et al 11 studied the influence of bus stop with left-turn lines between two adjacent signalized intersections based on a symmetric two-lane Nagel-Schreckenberg model, they found that the left-turn lines have a negative effect on the accident rate as well as delay if the stop is located close to the intersections. Juran et al 12 developed a dynamic traffic assignment model which could determine the impact of moving bottleneck.…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent tool, cellular automata (CA) models have been used widely to investigate the traffic flow behaviors. In particular, many researchers have studied the occurrence of car accidents by using the extended CA models, [16][17][18][19][20][21][22][23][24][25][26] e.g., the deterministic NS model proposed firstly by Boccara et al [20] Only the traffic influences of low visibility weather, e.g., foggy weather, on a freeway including the fraction of real vehicle rear-end accidents and road traffic capacity were studied by using the established CA model. The traffic flow model in rainy weather has not been established and the possible traffic accident has not been discussed.…”
Section: Introductionmentioning
confidence: 99%